Global diversity and distribution of three necrotrophic effectors in Phaeosphaeria nodorum and related species - McDonald, M.; Oliver, Richard; Friesen, T.; Brunner, P.; McDonald, B. (Wiley-Blackwell Publishing Ltd., 2013)
Population genetic and phylogenetic studies have shown that Phaeosphaeria nodorum is a member of a species complex that probably shares its center of origin with wheat (Triticum aestivum and Triticum durum). We examined the evolutionary histories of three known necrotrophic effectors (NEs) produced by P. nodorum and compared them with neutral loci. We screened over 1000 individuals for the presence/absence of each effector and assigned each individual to a multi-effector genotype. Diversity at each NE locus was assessed by sequencing c. 200 individuals for each locus. We found significant differences in effector frequency among populations. We propose that these differences reflect the presence/absence of the corresponding susceptibility gene in wheat cultivars. The population harboring the highest sequence diversity was different for each effector locus and never coincided with populations harboring the highest diversity at neutral loci. Coalescent and phylogenetic analyses showed a discontinuous presence of all three NEs among nine closely related Phaeosphaeria species. Only two of the nine species were found to harbor NEs. We present evidence that the three described NEs of P. nodorum were transmitted to its sister species, Phaeosphaeria avenaria tritici 1, via interspecific hybridization. © 2013 New Phytologist Trust.